Cooperative B–H bond activation: dual site borane activation by redox active κ2-N, S-chelated complexes. Issue 29 (6th July 2022) - Zafar, Mohammad; Ahmad, Asif; Saha, Suvam; Ramalakshmi, Rongala; Roisnel, Thierry; Ghosh, Sundargopal
Abstract : Redox-active ruthenium complexes supported by hemilabile κ 2 - N, S -chelated ruthenacycles undergo unusual dual site B–H bond activation through metal–ligand cooperation with free and bulky boranes. Abstract : Cooperative dual site activation of boranes by redox-active 1, 3- N, S -chelated ruthenium species, mer -[PR3 {κ 2 - N, S -(L)}2 Ru{κ 1 - S -(L)}], ( mer -2a : R = Cy, mer -2b : R = Ph; L = NC7 H4 S2 ), generated from the aerial oxidation of borate complexes, [PR3 {κ 2 - N, S -(L)}Ru{κ 3 - H, S, S ′-BH2 (L)2 }] ( trans – mer -1a : R = Cy, trans – mer -1b : R = Ph; L = NC7 H4 S2 ), has been investigated. Utilizing the rich electronic behaviour of these 1, 3- N, S -chelated ruthenium species, we have established that a combination of redox-active ligands and metal–ligand cooperativity has a big influence on the multisite borane activation. For example, treatment of mer -2a–b with BH3 ·THF led to the isolation of fac -[PR3 Ru{κ 3 - H, S, S ′-(NH2 BSBH2 N)(S2 C7 H4 )2 }] ( fac -3a : R = Cy and fac -3b : R = Ph) that captured boranes at both sites of the κ 2 - N, S -chelated ruthenacycles. The core structure of fac -3a and fac -3b consists of two five-membered ruthenacycles [RuBNCS] which are fused by one butterfly moiety [RuB2 S]. Analogous fac -3c, [PPh3 Ru{κ 3 - H, S, S ′-(NH2 BSBH2 N)(SC5 H4 )2 }], can also be synthesized from the reaction of BH3 ·THF with [PPh3 {κ 2 - N, S -(SNC5 H4 )}{κ 3 - H, S, S ′-BH2 (SNH4 C5 )2 }Ru], cis – fac -1c . In stark contrast, when mer -2b was treated with BH2 Mes (Mes = 2, 4, 6-trimethyl phenyl) it led to the formation of trans - and cis -bis(dihydroborate) complexes [{κ 3 - S, H, H -(NH2 BMes)Ru(S2 C7 H4 )}2 ], ( trans -4 and cis -4 ). Both the complexes have two five-membered [Ru–(H)2 –B–NCS] ruthenacycles with κ 2 -H–H coordination modes. Density functional theory (DFT) calculations suggest that the activation of boranes across the dual Ru–N site is more facile than the Ru–S one.